If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 2x + -1 + -3 = x + 8 Reorder the terms: -1 + -3 + X + 2x = x + 8 Combine like terms: -1 + -3 = -4 -4 + X + 2x = x + 8 Reorder the terms: -4 + X + 2x = 8 + x Solving -4 + X + 2x = 8 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + X + 4 + 2x = 8 + 4 + x Reorder the terms: -4 + 4 + X + 2x = 8 + 4 + x Combine like terms: -4 + 4 = 0 0 + X + 2x = 8 + 4 + x X + 2x = 8 + 4 + x Combine like terms: 8 + 4 = 12 X + 2x = 12 + x Add '-2x' to each side of the equation. X + 2x + -2x = 12 + x + -2x Combine like terms: 2x + -2x = 0 X + 0 = 12 + x + -2x X = 12 + x + -2x Combine like terms: x + -2x = -1x X = 12 + -1x Simplifying X = 12 + -1x
| 12x^11-15=0 | | 10/3=5/x | | 0.09xX=58.36 | | F(45)f(x)=6sinx | | 5/8x-8 | | 8x-14=2x+1 | | 10=-20-6y | | 9-7h=-9+2h | | 16=.75k+1 | | .5(2x+4)=2x | | 3x/4=80 | | 4x+2=3x+60 | | x/4-10=-7 | | -2x(5+7x)= | | 6x+5y=55 | | 2x+5+3x-2+3=84 | | x(-4+3x)= | | 9/7*67/42 | | 9y^3-11y^2+6y=11y^2-6y+17 | | -6(-2x+3)= | | pi*2=3.18 | | x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | -3x^2-21x+24= | | 5-4=30 | | 6x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | 8(5x-4)= | | 0.09xX=95.41 | | 2/3=3x/20 | | 3x-15=(2x+10) | | 6x+10=6x | | 2.7x+13.758=4-2.97x | | 4-2m+4m+1= |